Islamic versus western conceptions of knowledge - Sulaiman, Kabuye Uthman (Editorial of Al-Hikmah, 2022)
Islam has given great importance to knowledge acquisition, preservation, application and dissemination. It regards knowledge as one of the uncountable favours of Allah and His greatest gift to mankind. With knowledge, not only mankind can change the environment or create a civilization, but they are also able to distinguish reality from illusion, truth from falsehood or other alternatives. Despite the value of knowledge and its indispensability, there is a lack of consensus among epistemologists and philosophers as to what knowledge is and where it comes from or how it is acquired. This article sets out to: first, evaluate Plato’s view that knowledge is “justified true belief”; second define and explain the meaning of knowledge from the Islamic and Western perspectives; third, identify the ways of knowing or methods of acquiring knowledge, and; finally, describe the relationship between ‘ilm or the all-embracing Islamic epistemic term, and the following Islamic concepts: yaqin (certainty), iman (belief, faith or conviction which is based on reason and knowledge), taqwa (God-consciousness), hikmah (wisdom) and ma‘rifah (recognition of Allah, knowledge of the reality of things, etc.). This article is based on desk research and it draws on primary Islamic sources namely, the Qur’an and Hadith, as well as secondary works on the concept of knowledge from the Islamic and Western perspectives. Translation of the meanings of the selected verses from the Qur’an is based on ‘Abdullah Yusuf ‘Ali’s Translation of the Meaning of the Qur’an except in a few places where other translations seemed more appropriate. After reading this exposition of knowledge, one should be able to: (a) explain the meaning and concept of knowledge from the Islamic and Western perspectives, (b) examine the relationship between knowledge and information, and ‘ilm and taqwa, ma‘rifah, iman and hikmah, and (c) differentiate between the Islamic and Western perspectives of knowledge.